1979
DOI: 10.7326/0003-4819-90-4-664
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of the Legionnaires' Disease Bacterium from Environmental Samples

Abstract: We analyzed 24 environmental samples collected in or near the Indiana Memorial Union, where an epidemic of Legionnaires' disease occurred in early 1978. We conducted fluorescent antibody analyses and culture on F-G and charcoal yeast extract agars of each sample directly; splenic tissue of guinea pigs inoculated with the sample; and yolk sacs from embryonated eggs inoculated with splenic tissue of guinea pigs injected with the sample. Legionnaires' disease (LD) bacterium was isolated from seven of the 24 sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0
2

Year Published

1980
1980
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(58 citation statements)
references
References 9 publications
1
55
0
2
Order By: Relevance
“…Environmental surveys in this country and the U.S.A. indicate that the organism is widespread in nature. It has been recovered from mud, rivers, lakes and other natural collections of water (Morris et al 1979;Fliermans et al 1979;Fliermans et al 1981) and it is clear that the bacterium is also present in man-made water systems. It has been found in domestic water and recirculating cooling water systems (Morris et al 1979;Tobin, Swann and Bartlett, 1981;Cordes et al 1981).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental surveys in this country and the U.S.A. indicate that the organism is widespread in nature. It has been recovered from mud, rivers, lakes and other natural collections of water (Morris et al 1979;Fliermans et al 1979;Fliermans et al 1981) and it is clear that the bacterium is also present in man-made water systems. It has been found in domestic water and recirculating cooling water systems (Morris et al 1979;Tobin, Swann and Bartlett, 1981;Cordes et al 1981).…”
Section: Introductionmentioning
confidence: 99%
“…It has been recovered from mud, rivers, lakes and other natural collections of water (Morris et al 1979;Fliermans et al 1979;Fliermans et al 1981) and it is clear that the bacterium is also present in man-made water systems. It has been found in domestic water and recirculating cooling water systems (Morris et al 1979;Tobin, Swann and Bartlett, 1981;Cordes et al 1981). The importance of each as a source of L. pneumophila infections is not known but the prevalence ofthe bacterium in cooling water systems makes them important potential sources.…”
Section: Introductionmentioning
confidence: 99%
“…Legionella pneumophila, the causative agent of Legionnaires' Disease, has been reported to be prevalent in both man-made and natural aquatic environments (Fliermans et al 1979Fliermans 1984;Morris et al 1979;Tison et al 1980). Numerous studies have indicated a strong association of the incidence of legionel losis with cooling systems (e.g., cooling towers, exchangers, and wash systems) (Orrison, Cherry, and Milan 1981;Cordes et a1 .…”
Section: Prevalence Of Legionel La In Aquatic Environmentsmentioning
confidence: 99%
“…Legionella are flagellated Gram-negative bacteria that belong to the class of gamma-proteobacteria. They are ubiquitously present in water habitats, including natural and man-made reservoirs [14,37] where they infect and parasitize protozoa [1,45]. In the host, a specialized compartment is formed, that enables replication of Legionella [6].…”
Section: Introductionmentioning
confidence: 99%